Pengaruh Penambahan Nanokatalis MnFe2O4 Terhadap Proses Pirolisis Sampah Plastik HDPE - Wati, Rita Fajar; Wardana, ING; Winarto, Winarto; Sukarni, Sukarni; Puspitasari, Poppy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
The effects of MnFe2O4 nanocatalyst addition toward HDPE plastic waste pyrolysis have been investigated by performing experiments on METTLER TOLEDE TGA DSC1 Simultaneous Thermal Analyzer at heating rates of 10oC/min by nitrogen and temperatures range from room temperature to 1000oC. The results of pyrolysis showed that the main polymer components of HDPE plastic waste, both, with and without MnFe2O4 nanocatalyst addition degraded in one stage. The MnFe2O4 nanocatalyst addition increases the maximum mass loss rate of HDPE plastic waste pyrolysis, however, it increase the degradation of the initial temperature.